Assessment of a TEC calibration procedure by single-frequency PPP - Prol, Fabricio dos Santos [UNESP]; Camargo, Paulo de Oliveira [UNESP]; Monico, João Francisco Galera [UNESP]; Muella, Marcio Tadeu de Assis Honorato (Springer Nature, 2018)
Global navigation satellite system (GNSS) measurements have become an outstanding data source for ionospheric studies using total electron content (TEC) estimation procedures. Many methods for TEC estimation had been developed over recent decades, but none of them is capable of providing high accuracy for the single-frequency precise point positioning (PPP). We present an analysis of the performance of a new TEC calibration procedure when applied to PPP. TEC estimation is assessed by calculating the improvements obtained in single-frequency PPP in kinematic mode. A total of 120 days with six distinct configurations of base and rover stations was used, and the TEC performance is assessed by applying the estimated TEC from the base station to correct the ionospheric delay in a nearby rover receiver. The single-frequency PPP solution in the rover station reached centimeter accuracy similar to the ionospheric-free PPP solution. Further, the TEC calibration method presented an improvement of about 74% compared to the PPP using the global ionospheric maps. We, therefore, confirm that it is possible to estimate high-precision TEC for accurate PPP applications, which enables us to conclude that the principal challenge of the GNSS community developing ionospheric models is not the differential code bias or the temporal variation of the ionosphere, but the development of methods for accurate spatial interpolation of the slant TEC.
Keywords: DCB; GIM; GPS; Ionospheric delay; Kinematic PPP